Ion-exchange resin as a new tool for characterisation of coordination compounds and MOFs by NMR spectroscopy. Issue 56 (24th June 2019) - Galaço, Ayla Roberta Borges da Silva; de Oliveira, Kleber Thiago; Donatoni, Maria Carolina; Walton, Richard I.; Serra, Osvaldo Antonio
Abstract : 1 H and 13 C NMR spectroscopy is used to investigate the organic constituents of paramagnetic MOFs and coordination compounds using a cationic exchange resin. Post-modifications on MOFs were performed and quantitatively determined by this methodology. Abstract : 1 H and 13 C NMR spectroscopy is used to investigate the organic constituents of metal complexes, MOFs and coordination compounds synthesised under solvothermal and precipitation conditions. The elucidation of the ligands in paramagnetic compounds bearing Cu 2+ (d 9 ), Gd 3+ (f 7 ), Eu 3+ (f 6 ), Fe 3+ (d 5 ), ions after treatment with a cationic exchange resin is possible. We prove the efficiency of two post-synthesis linker modifications on diamagnetic IRMOF-3 Zn 2+ (d 10 ) with ethyl isocyanate and benzyl bromide.